Development of tungsten (VI) trioxide-based saturable absorber for mode-locked fiber laser - Abdul Hadi, Muhamad Amir Waliuddin (2020)
The current research on passive mode-locked fiber lasers (MLFL) has delved into various nanomaterials in the fabrication of SAs, and more recently, transition metal oxides (TMO). Among the TMO, tungsten trioxide (WO3) has unique advantages such as fast response time, high electron density and mobility, good thermal and mechanical stability, as well as enhanced nonlinear optical absorption with increasing irradiance. Despite the low cost, non-toxic characteristics, and vast employment for various applications, WO3 has yet to be employed to generate mode-locked pulse generation. This investigation looks into the development of WO3 as a saturable absorber (SA) for the generation of mode-locked pulses. Tapered single mode fiber with adiabatic characteristics (parameters: 20-0.5-20-10) of 1 dB maximum transmission loss was used in this work. A WO3 nanocomposite of varying concentrations from 0.005-1.28 wt% were prepared by mixing sonicated WO3 with polydimethylsiloxane (PDMS). The synthesized nanocomposite was then deposited on tapered fiber and cured. From the material characterizations, the sonicated WO3 has monolithic crystal structure with band gap of 2.8 eV. The elemental composition characterization proved the presence of WO3 in the PDMS matrix. However, the working range of the SA to produce mode-locked pulses is only from 0.025-1.103 wt% composite. The nonlinear saturable characterization of the SAs revealed a modulation depth varying from 0.75-4.3 %, nonsaturable loss from 23.13- 60.06 %, and saturation intensity from 0.39-4.50 MW/cm². An erbium-doped fiber ring laser (EDFL) scheme was constructed for the integration of the SA and was optimized to operate in the C-band with a net anomalous dispersion. 0.65 wt % SA was integrated and chosen for further investigation as it represented the mid-range of the concentrations. The laser scheme successfully demonstrated mode-locked conventional soliton generation. The repeatability in performance of the SA was also investigated by fabricating another four samples with similar methods, concentration, and testing environment. The repeatability results revealed small standard deviations which validated the reproducibility of the SA. The influence of the WO3 concentration on the pulse performance was also investigated. It was deduced that the pulse performance is not be dependent on the concentration and the possible reasons behind this was discussed. From these results, 0.03 wt % SA showed remarkable performance; shortest pulse duration (98 fs) with broadest 3 dB-bandwidth spectrum (26.65 nm). Therefore, 0.03 wt % was selected for in-depth investigation similar to that performed on the 0.65 wt % SA. The 0.03 wt % SA demonstrated conventional solitons transitioning to become stretched pulse with increasing pump power. Calculation of the time bandwidth product (TBP) also revealed that the quality of pulse at 190 mW pump power. A comparison between these two SAs reveal two distinct applications; an SA for simple and stable conventional mode-locking and a SA for switchable mode-locking between solitons and stretched pulses.